Agro-town Development as a Technology of Life Support and Socio-economic Policy of the Country - Prokhorova, Victoria V.; Zakharova, Elena N.; Gladilin, Alexandr V.; Molchan, Alexey S. (International Review of Management and Marketing, 2016)
The paper suggests an idea of agro-town (agro-territory) development in Russia be considered and a tendency of development of successful projects in this sphere be analyzed. The material uses such definitions as “agro-town”, “agro-territory”, “infrastructure”, “agro-industrial complex”. When investigating the issues concerning agro-town formation and development it is important to draw on experience of foreign countries. Creation and promotion of the project “agro-town” demands capture of young researches scientific being on agrarian technical colleges, theorists and practitioners of agribusiness and also corroboration of statutory instrument base state support. Agro-business development is an important condition for life support in the country. Agro-towns are one of the priorities of agro-business investment appeal (agro-industrial complex). Keywords: agro-town, agro-industrial complex, socio- economic appeal, competitiveness, innovative projects of agriculture development JEL Classifications: Q01, Q18, Q28